2022
DOI: 10.1002/smll.202106757
|View full text |Cite
|
Sign up to set email alerts
|

Progress of GaN‐Based Optoelectronic Devices Integrated with Optical Resonances

Abstract: are even smaller, only a few MHz, which are far away from the requirement of fast and large data wireless transmission for VLC. [5] To enhance the data transmission rates, complex modulation schemes and/ or equalization have to be utilized, which, however, hinder the further developments and applications. In addition, Si-based optoelectronic devices, like Si PDs, a bluefiltering technology are still used currently for shorter wavelength visible light detection, which suffers from complexity and low light trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 148 publications
0
14
0
Order By: Relevance
“…In addition to the above mentioned applications, novel photonic structures are being designed for exploiting Tamm plasmons for various new applications in active & passive optoelectronics [195][196][197], resonant cavity LEDs [194], solar thermophotovoltaics [198], and organic solar cell [199][200][201]. For example, a simple and effective strategy using hybrid TPP-MC modes as shown in Fig.…”
Section: Other Applicationsmentioning
confidence: 99%
“…In addition to the above mentioned applications, novel photonic structures are being designed for exploiting Tamm plasmons for various new applications in active & passive optoelectronics [195][196][197], resonant cavity LEDs [194], solar thermophotovoltaics [198], and organic solar cell [199][200][201]. For example, a simple and effective strategy using hybrid TPP-MC modes as shown in Fig.…”
Section: Other Applicationsmentioning
confidence: 99%
“…This work is dedicated to a comprehensive study to explore plasmon formation in coupled and uncoupled GaN nanowires. GaN is a well-known material for its electronic and optoelectronic applications [26,27]. The hybrid semiconducting structures comprising GaN exhibits excellent device grade optical properties [28].…”
Section: Introductionmentioning
confidence: 99%
“…Looking back on past 30 years of intensive and vast studying of GaN, it can be incontestably concluded that they catapulted GaN to the position of one of the fundamental materials for modern (opto)­electronics. , Among the game-changing GaN-based devices blue light emitting diode (LED) and high electron mobility transistor (HEMT) must be emphasized, but photodetectors, lasers, power devices and quantum electronics , have to be evoked as well. Devices integrated with optical resonances like photonic crystals, distributed Bragg reflectors, or microdiscs may state another examples of GaN-based optoelectronics. What is also worthwhile to bring to the fore is the up-to-date scientific interest in combining GaN with more in vogue materials such as graphene, transition metals dichalcogenides, or perovskites, which is demonstrated in reports concerning graphene/GaN LEDs, gas sensors, and photodetectors; GaN/MoS2 light emitters and WS 2 /GaN photodetectors; InGaN/GaN/CsPbBr 3 /FAPbBr 3 and CsPbI 3 /GaN light emitters; , or planar solar cells. Among other examples of van der Waals crystal/GaN-based devices, the h-BN/GaN pair was introduced as a building block in h-BN/GaN Schottky diodes, , light emitting diodes, photodetectors, or transistor structures .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Among the game-changing GaNbased devices blue light emitting diode (LED) 3 and high electron mobility transistor (HEMT) 4 must be emphasized, but photodetectors, 5−8 lasers, 9−12 power devices 13 and quantum electronics 2,14 have to be evoked as well. Devices integrated with optical resonances like photonic crystals, distributed Bragg reflectors, or microdiscs 15 may state another examples of GaN-based optoelectronics. What is also worthwhile to bring to the fore is the up-to-date scientific interest in combining GaN with more in vogue materials such as graphene, transition metals dichalcogenides, or perovskites, which is demonstrated in reports concerning graphene/GaN LEDs, 16 gas sensors, 17 and photodetectors; 18 GaN/MoS2 light emitters 19 and WS 2 /GaN photodetectors; 20 InGaN/GaN/ CsPbBr 3 /FAPbBr 3 and CsPbI 3 /GaN light emitters; 21,22 or planar solar cells.…”
Section: ■ Introductionmentioning
confidence: 99%